CoWIN: The future of universal immunization program in India - M C Arjun; Arvind Kumar Singh; Swayam Pragyan Parida (Wolters Kluwer Medknow Publications, 2023)
CoWIN (Covid Vaccine Intelligence Network) is a web-based platform owned and operated by the Government of India for facilitating COVID-19 vaccination of the citizens. This project is considered a tremendous success, apparent from the sheer number of hassle-free and successful COVID-19 vaccinations. We believe that the CoWIN system is an ideal platform for capturing all the vaccine-related data in the Universal Immunization program (UIP) as well as providing an all-inclusive vaccine certificate in digital format. Advantages and challenges of upscaling the CoWIN system to include UIP and a vision statement of how this can be achieved are discussed in this article. We also enlist the state-level solutions currently in use for digital immunization records, which can serve as case studies for upscaling the CoWIN system.